Awareness and Practice of Disaster Risk Reduction and Management: Foundations for Teacher Training (Architecture Image Studies, 2025)
With a focus on the four disaster themes of disaster rehabilitation and recovery, disaster response, disaster preparedness, and disaster prevention and mitigation, the study aims to investigate the degree of awareness and implementation of disaster risk reduction and management (DRRM) within the comprehensive school safety framework among secondary public school teachers. The study also aims to ascertain if awareness and DRRM implementation levels in educational contexts are significantly correlated. The respondents consisted of 236 secondary school teachers during the 2022-2023 academic year. The findings revealed that teachers did not demonstrate a strong level of awareness and implementation of DRRM within the comprehensive school safety framework across the four disaster themes. Although a significant correlation was confirmed between the level of awareness and the level of implementation of DRRM in school settings, the study highlights that this does not guarantee effective implementation of the four disaster themes by schools and teachers in practice.